THE EFFECT OF USING CHINESE WHISPERS GAME ON STUDENTS’ VOCABULARY MASTERY - Reza Oktaviana Pasaribu (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The research aimed to 1) describe the applying chinese whispers game on students’ vocabulary mastery, 2) describe students’ vocabularymastery before and after applying chinese whispers game, and 3) whether there was a significant effect of applying chinesewhispers game on students’ vocabulary mastery at the eighth grade of SMP Negeri 2 Angkola Selatan.This research used experimental method by using pre-experimental research design (one group pretest-posttest design). Thepopulation was the eighth grade students which consist of 128students and the samples were32 students which taken by using purposive sampling technique. In collecting the data, the researcher used observation in chinese whispers game on students vocabulary mastery and test for students’ vocabulary mastery before and after using chinese whispers game. Based on descriptive analysis, the result showed 1) the average of Chinese whispers game on vocabulary mastery was 3.5 (very good category) and 2) the average of students’ vocabulary mastery before applying Chinesewhispers game was 29.34 (fail category) and after applying Chinese whispers game was 65.18 (enough category). To know the result of the data, the researcher analysis data by use the formula of ttest = 35.79, meanwhile ttable 2.04. It means that ttest is higher than ttable. So the hyphothesis is accepted. It means that there is significant effect of chinese whispers game on students vocabulary mastery at the eighth grade students of SMP Negeri 2 Angkola Selatan. Keywords: Chinese Whispers Game, VocabularyMastery Abstrak: Penelitian ini bertujuan untuk 1) mendeskripsikan penerapan chinese whispers game dalam penguasaan kosakata siswa, 2) mendeskripsikan penguasaan kosakata siswa sebelum dan sesudah penerapan chinese whispers game dan 3) apakah terdapat pengaruh yang signifikan antara chinese terhadap penguasaan kosakata siswa pada kelas VIII SMP Negeri 2 Angkola Selatan. Penelitian ini menggunakan metode eksperimen dengan menerapkan penelitian pra eksperimental (one group pretest-posttest design). Populasi dalam penelitian ini adalah siswa kelas VIII yang terdiri dari 128 siswa dan sampelnya adalah 32 siswa yang diambil dengan menggunakan teknik purposive sampling. Dalam pengumpulan data, peneliti menggunakan observasi dalam penerapan Chinese whispers game dan tes dalam penguasaan kosakata siswa sebelum dan sesudah menggunakan chinese whispers game. Berdasarkan analisis deskriptif, diperoleh hasil 1) rata-rata penerapan chinese whispers game dalam penguasaan kosakata 3.5 (kategori sangat baik) dan 2) rata-rata kosakata siswa sebelum penerapan Chinesewhispers game adalah 29,34 (kategori gagal) dan setelah penerapan chinese whispers game adalah 65.18 (kategori cukup). Peneliti menganalisi data menggunakan ttest formula, hasil ttest 3= 35.79, sedangkan ttable = 2.04. dengan kata lain ttest lebih besar dari ttable. Jadi, hipotesis diterima. Artinya ada pengaruh yang signifikan dari chinese whispers game dalam penguasaan kosakata siswa pada kelas VIII SMP Negeri 2 Angkola Selatan Kata kunci: chinese whispers game, kosakata.